Improving Learning Outcomes of Class III Students in Mathematics Subjects Through the Teams Games Tournament (TGT) Model of SD 3 Jepang - Rohmah, Dwi Putri Khabibatur; Sa'diyah, Isnaini Khalimatus; Riswari, Lovika Ardana (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2024)
Introduction/Main Objectives: This research aims to determine the improvement in mathematics learning outcomes of students in class III at SD III Jepang Mejobo Kudus after the Team Games Tournament learning model was implemented. The research was conducted because the learning process and student learning outcomes were low and students appeared passive. Therefore, researchers took action to improve learning using the Team Games Tournament learning model. Research Methods: This research uses the Classroom Action Research method. The subjects of this research were 19 grade III students of SD 3 Jepang Mejobo. This research is classroom action research which consists of two cycles with the steps of implementing action, observation, and reflection. In this study, researchers collaborated with direct observers during the actions and results of student ability tests. Finding/Results: Based on data analysis of student learning outcomes, it shows an increase in the completeness of student learning outcomes with details namely pre-cycle (31.57%), cycle I (47.36%), and cycle II (73.68%). Student learning activities also increased as shown by the results of 59.21% of active students in cycle I then rising to 72.10% in cycle II. This research concludes that the use of the Team Games Tournament learning model can improve student mathematics learning outcomes and student activity.